2007
DOI: 10.1196/annals.1422.061
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in Nonautoimmune Individuals during Infections

Abstract: Infections can act as environmental triggers inducing or promoting autoimmune disease in genetically predisposed individuals. Identification of microbial peptides similar to self-tissues may by molecular mimicry, provide the inducing mechanism for an immune response. The aim of this study was to identify autoantibodies (autoAbs) in nonautoimmune individuals during acute bacterial, viral, or parasitic infections. Specific Abs or specific infections with an increased autoAb load may shed insight into the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…However, most of the time viruses do not induce autoimmunity. It is not uncommon to see some self-reactive antibodies generated during infection (43)(44)(45), but most of the time the host survives a viral infection without serious autoimmune manifestations. It was, therefore, of interest to determine whether Foxp3 ϩ CD4 ϩ natural Treg cells, present at the beginning of viral infections, were resistant or sensitive to the T cell apoptosis that occurs early during infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the time viruses do not induce autoimmunity. It is not uncommon to see some self-reactive antibodies generated during infection (43)(44)(45), but most of the time the host survives a viral infection without serious autoimmune manifestations. It was, therefore, of interest to determine whether Foxp3 ϩ CD4 ϩ natural Treg cells, present at the beginning of viral infections, were resistant or sensitive to the T cell apoptosis that occurs early during infection.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we could not totally relate our patients' acute hemolysis to postinfectious autoimmune hemolytic anemia. Berlin and associates [4] reported that in nonautoimmune individuals with various infections, elevated titers of autoantibodies could be detected by molecular mimicry of microbial peptides similar to self-tissues. The transient nature of the autoantibodies in our patients could be explained by this.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of direct Coombs' tests were negative, both patients reported here had the presence of autoimmune antibodies such as ANA, SMA, and antidsDNA. In genetically predisposed individuals, infections could act as environmental triggers inducing or promoting autoimmune disease [4]. It has been suggested that acute hepatitis A virus infection induces autoimmune hemolytic anemia [15].…”
Section: Discussionmentioning
confidence: 99%
“…25 A 2007 study examined blood sera from 88 patients with acute infections (41 bacterial, 23 viral, 17 parasitic and 7 rikettsial). 26 Elevated titers of autoantibodies including annexin V, prothrombin, anti-Saccharomyces cerevisiae antibody, antinuclear antibody (ANA) or antiphospholipid antibodies were detected in about 50% of the subjects, with 34 individuals harboring elevated titers of at least two autoantibodies.…”
Section: Communities Of Microbes Drive Autoimmune Diseasementioning
confidence: 99%